George Eliot - Collins, K. author. aut Link
XXIV, 280 p.
Keywords: Spanning her entire life, the fully annotated selections in this volume include well known recollections of the great Victorian novelist plus a large assortment not found in her biographies. Altogether they provide a fresh, vivid, and sometimes startling portrait of a controversial genius.